2016
DOI: 10.1016/j.jmii.2014.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Anti-ST2 monoclonal antibody inhibits eosinophil infiltration in Angiostrongylus cantonensis-infected mice

Abstract: The IL-33/ST2 axis may play a crucial role in the pathogenesis of angiostrongylosis and the results of this study could be useful for the development of strategies to reduce the neurological damage caused by this parasitic infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…The injection of a monoclonal anti-ST2 antibody 3 days postinfection with further injections every 5 days led to a significant reduction of IL-5 blood levels and of eosinophil influx in the meninges (82). Thus, blocking the IL-33/ST2 axis could be beneficial in minimizing the neurological damage caused by this parasitic infection (82). In summary, the IL-33/ST2 pathway is activated in numerous tissues, where it manages the initiation and progression of a Th2 immune response that can promote protective worm expulsion.…”
Section: Role Of Il-33/st2 In Helminth Diseasesmentioning
confidence: 97%
See 1 more Smart Citation
“…The injection of a monoclonal anti-ST2 antibody 3 days postinfection with further injections every 5 days led to a significant reduction of IL-5 blood levels and of eosinophil influx in the meninges (82). Thus, blocking the IL-33/ST2 axis could be beneficial in minimizing the neurological damage caused by this parasitic infection (82). In summary, the IL-33/ST2 pathway is activated in numerous tissues, where it manages the initiation and progression of a Th2 immune response that can promote protective worm expulsion.…”
Section: Role Of Il-33/st2 In Helminth Diseasesmentioning
confidence: 97%
“…In this model, splenocytes and mononuclear brain cells responded to IL-33 through production of IL-5 and IL-13, both of which contribute to eosinophilic meningitis induced by A. cantonensis (80,81). The injection of a monoclonal anti-ST2 antibody 3 days postinfection with further injections every 5 days led to a significant reduction of IL-5 blood levels and of eosinophil influx in the meninges (82). Thus, blocking the IL-33/ST2 axis could be beneficial in minimizing the neurological damage caused by this parasitic infection (82).…”
Section: Role Of Il-33/st2 In Helminth Diseasesmentioning
confidence: 98%
“…58 In another antagonistic strategy, anti-ST2 antibody decreased eosinophilic response and meningitis caused by Angiostrongylus systemic parasitic infection. 59 Blockade of IL-33 prevented chronic systemic lupus erythematosus in lupus-susceptible mice by inhibition of T H 17, proinflammatory cytokines, and recruitment of Treg cells. 60 In respiratory diseases, blocking of IL-33 activity proved to be more effective.…”
Section: Beneficial Effects Of Blocking Il-33 or St2 In Different Dismentioning
confidence: 99%
“…More recently, it was demonstrated that treatment of mice with anti-CCR3 monoclonal antibody, which is abundant on the surface of eosinophils and is responsible for their activation and chemotaxis, reduced the infiltration of eosinophils and the severity of eosinophilic meningitis (Chuang et al, 2010). A similar picture is seen when mice are treated with anti-ST2 monoclonal antibodies, which blocks the IL-33/ST-2 pathway and inhibits the production of IL-5 (Chuang et al, 2014). The authors speculated that the central function of eosinophils may involve tissue remodeling, repair, and immune regulation (Chuang et al, 2014; Chuang et al, 2010; Gosnell and Kramer, 2013).…”
Section: The Pathogenesis Of Neurological Dysfunctionmentioning
confidence: 60%
“…A similar picture is seen when mice are treated with anti-ST2 monoclonal antibodies, which blocks the IL-33/ST-2 pathway and inhibits the production of IL-5 (Chuang et al, 2014). The authors speculated that the central function of eosinophils may involve tissue remodeling, repair, and immune regulation (Chuang et al, 2014; Chuang et al, 2010; Gosnell and Kramer, 2013). Taken together, these observations indicate that eosinophils have a complex role in the disease pathogenesis requiring further studies.…”
Section: The Pathogenesis Of Neurological Dysfunctionmentioning
confidence: 60%